2010
DOI: 10.1007/s12228-009-9103-y
|View full text |Cite
|
Sign up to set email alerts
|

Kadua haupuensis (Rubiaceae: Spermacoceae), a new endemic species from Kaua’i, Hawaiian Islands

Abstract: Abstract. The new species Kadua haupuensis is described and illustrated from the isolated Mt. Ha'upu region of Kaua'i, Hawaiian Islands. This new species belongs to Kadua subg. Kadua sect. Wiegmannia. It is characterized by a subdioecious (leaky dioecious) breeding system and appears most closely related to another apparently dioecious species endemic to Kaua'i, Kadua flynnii, with which it is compared. Although the only original wild population is critically endangered and may possibly be extinct, this new sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Rigorous botanical research conducted over the past few decades by staff of the NTBG has contributed 28 new taxa to the flora of Kaua'i (Lammers & Lorence 1993, Wagner et al 1994, 1996, Lorence 1996, Carr & Lorence 1998, Wagner & Lorence 1998, Wagner 1999, Wood & Wagner 1999, Lowry & Wood 2000, Lorence & Gemmill 2004, Lorence et al 2010 increasing the island's previously known SIE level by 12.5%. Many of those species represent endemic genera, and all of them are on the brink of extinction.…”
Section: Discussionmentioning
confidence: 99%
“…Rigorous botanical research conducted over the past few decades by staff of the NTBG has contributed 28 new taxa to the flora of Kaua'i (Lammers & Lorence 1993, Wagner et al 1994, 1996, Lorence 1996, Carr & Lorence 1998, Wagner & Lorence 1998, Wagner 1999, Wood & Wagner 1999, Lowry & Wood 2000, Lorence & Gemmill 2004, Lorence et al 2010 increasing the island's previously known SIE level by 12.5%. Many of those species represent endemic genera, and all of them are on the brink of extinction.…”
Section: Discussionmentioning
confidence: 99%
“…The retention of neutral red in the corolla lobes, anthers, and stigma of both long-and short-styled floral morphs of G. scabra suggests that these structures are the primary source of the flower's scent. The presence of scent-emitting regions in flowers is a common trait in the Rubiaceae family, where many species, including Psychotria homalosperma [35], Hillia parasitica [16], Faramea cyanea [36], Isertia laevis [37], Kadua haupuensis [38], and Randia itatiaiae [39] produce fragrant flowers whose scent is thought to mediate pollinator attraction. While flower scent production can involve the entire blossom, it is often concentrated in specific regions or structures [40], with petals generally being the main source of VOCs responsible for the fragrance [40][41][42].…”
Section: Scent Emission Within the Flowermentioning
confidence: 99%
“…However, results from a recent study of Hawaiian species of Kadua , focusing on capsule and seed morphology, revealed that these characters of Hawaiian and certain South Pacific species are distinct from other Asian and western Pacific species of Hedyotis , and consequently they have been transferred to the genus Kadua ( Terrell et al 2005 ). Kadua now comprises some 30 species including this new species and Kadua haupuensis Lorence & W. L. Wagner, a new species recently described from Kaua`i ( Lorence et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%